Abnormal Cerebrospinal Fluid Cytology in Functional Movement Disorders - Serranová, Tereza; Slovák, Matěj; Forejtová, Zuzana; Sieger, Tomáš; Dušek, Petr; Srpová, Barbora; Mrázová, Kateřina; Růžička, Evžen; Šonka, Karel; Espay, Alberto J; Nytrová, Petra (Psychosomatic medicine, 2024)
OBJECTIVE: The role of inflammation and neuroimmune mechanisms, which have been documented in various neuropsychiatric disorders including the seizure subtype of functional neurological disorder, remains unclear in functional movement disorders (FMD). To explore these mechanisms, we analyzed selected inflammatory markers in cerebrospinal fluid (CSF) in patients with FMD. METHODS: We compared CSF markers in 26 patients with clinically established FMD (20 females; mean [SD] age = 43.3 [10.9], disease duration = 3.9 [3], range = 0.1-11 years; mean follow-up after lumbar puncture = 4.3 [2] years, range = 0.5-7 years) and 26 sex- and age-matched clinical controls with noninflammatory nonneurodegenerative neurological disorders, mostly sleep disorders. RESULTS: Sixty-five percent of FMD patients versus 15% of controls showed cytological abnormalities (i.e., increased white blood cells [WBC] count, signs of WBC activation, or both; odds ratio [OR] = 9.85, 95% confidence interval = 2.37-52.00, p < .01, corrected), with a significantly higher frequency of an isolated lymphocytic activation, 35% versus 0% (OR = ∞, 95% confidence interval = 2.53-∞, p < .05, corrected). There were no differences in CSF protein and albumin levels, quotient albumin, IgG index, and oligoclonal bands. CSF abnormalities were not associated with more severe motor symptoms or a higher frequency of depression in FMD. CONCLUSIONS: Our results suggest a possible involvement of immune mechanisms in the pathophysiology of (at least a subtype of) FMD that deserves further investigation.
Keywords: konverzní poruchy; cytodiagnostika; Male; biologické markery; pohybové poruchy; Biomarkers; Conversion Disorder; Adult; dospělí; mužské pohlaví; Movement Disorders; počet leukocytů; Cytodiagnosis; Leukocyte Count; lidé; ženské pohlaví; Humans; Female; lidé středního věku; Middle Aged